Applications of environmental aquatic chemistry : a practical guide - Weiner, Eugene R. (Boca Raton : CRC Press, 2013)
'Preface to the Third Edition The chemical makeup of a collected water sample reflects the history of its prior flow path, particularly the minerals it has contacted, its contact time with these minerals, and the values of temperature, pH, and redox potential along the flow path. Many environmental chemistry books can be put into one of two groups: 1. Those that are very thorough and include nearly all of the basic chemical principles that underlie the topics covered. 2. Those that rely on an existing understanding of the basic principles and begin from there. This text tries to follow a middle path, where the basic principles needed for an environmental topic are included only to the extent of contributing to an understanding of the topic being discussed and to guide the reader in applying the information to actual environmental problems. The fields of environmental science and engineering advance rapidly. This third edition is substantially updated (Photo courtesy of Gary Witt) viii Preface to the Third Edition from the second edition. Besides extensive reorganization and updating, there is a new chapter'Nutrients and Odors: Nitrogen, Phosphorus, and Sulfur,' two new appendices'Solubility of Slightly Soluble Metal Salts' and'Glossary of Acronyms and Abbreviations Used in this Book,' and much new material, especially in Chapters 5 and 11 and in Appendix A.'--
ch. 1. Water quality -- ch. 2. Contaminant behavior in the environment : basic principles -- ch. 3. Major water quality parameters and applications -- ch. 4. Nutrients and odors : nitrogen, phosphorus, and sulfur -- ch. 5. Behavior of metal species in the natural environment -- ch. 6. Soil, groundwater, and subsurface contamination -- ch. 7. General properties of nonaqueous phase liquids and the behavior of light nonaqueous phase liquids in the subsurface -- ch. 8. Behavior of dense nonaqueous phase liquids in the subsurface -- ch. 9. Biodegradation and bioremediation of LNAPLs and DNAPLs -- ch. 10. Behavior of radionuclides in the water and soil environment -- ch. 11. Selected topics in environmental chemistry.
Includes bibliographical references and index.
Mode of access : World Wide Web.
Keywords: Environmental chemistry; Water quality